Literal, Antiliteral, and Mythological Religious Orientations - Poythress, Norman Godfrey (Journal for the scientific study of religion, 1975)
A sample of 234 college undergraduates were clustered into relatively homogeneous religious types based on the similarity of their religious profiles on three scales of religious commitment delineated by Hunt (1972): Literal, Antiliteral, and Mythological. Consistent with Hunt's previous notions, the Mythological commitment was a prominent one among subjects tested. However, a second contention of Hunt's -- that proreligious subjects of different substantive orientations might differ in terms of personality characteristics -- was not supported. Literally-oriented religious Believers did not differ significantly from Mythologically-oriented Believers on measures of intelligence, authoritarianism, or racial prejudice. Religious Believers as a group were found to be significantly less intelligent and more authoritarian than religious Skeptics.